Understanding the effects of democracy status and political risks to the volatility of the stock market returns in the Philippines - Tomo, Ivanah Irene Michaela M. (School of Economics, University of the Philippines Diliman, 2019)
The Philippine political system and economic landscape have always been unique and colorful. They have been molded by different positive and negative events that have been marked historically. The current situation and the future perspective of the people with regards to the politics and economy in the Philippines are not only influenced by the history, but also by the different internal and external factors that they are experiencing. The Philippines is now once again living in a very exciting and uncertain time. Philippine politics, and its stakeholders are active and involved now more than ever. It is important to recognize that factors in the macro_level like the politics and economics may affect each other and a change in one can have an implication to another. This research aims to contribute more to the broad studies on the relationship of politics and economics by studying the effect of the Democracy Ratings and Political Risks to the volatility of the stock market returns of the Philippines from year 1995 to 2017. The results of the research show that the lower the political risk, the lower the volatility of the stock returns. The researcher believes that the study will be helpful in establishing a clearer relationship between politics and the behavior of stock market.